2010
DOI: 10.1007/s00216-010-3535-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of sensitivity-improved fluorescence-linked immunosorbent assay using a fluorescent single-domain antibody against the bioactive naphthoquinone, plumbagin

Abstract: A fluorescent single-domain antibody (fluobody), a fusion protein of a green fluorescent protein extracted from Aequorea coerulescens (AcGFP), a mutant that has been codon-optimized for mammalian expression, and a single-chain variable fragment antibody (scFv), against plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone; PL) was successfully constructed and expressed in Escherichia coli. The expressed fluobody was purified, refolded, and characterized to develop a speedy, simple, and sensitive fluorescence-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
1
14
0
3
Order By: Relevance
“…10 The previous research supposed that the highly sensitive fluorescence of AcGFP detected by the fluorescent microplate reader contributed to the improvement in sensitivity and this is consistent with our results. 21,22 The cross-reactivity values for other AVMs in the optimized FLISA were all consistent with that in traditional colorimetric ELISA method, while lower IC 50 in the FLISA was obtained (table 2). All these data showed that a one-step FLISA could be developed by using fluobody instead of monoclonal antibody.…”
Section: Comparison Of the Developed Flisa And Traditional Elisasupporting
confidence: 81%
“…10 The previous research supposed that the highly sensitive fluorescence of AcGFP detected by the fluorescent microplate reader contributed to the improvement in sensitivity and this is consistent with our results. 21,22 The cross-reactivity values for other AVMs in the optimized FLISA were all consistent with that in traditional colorimetric ELISA method, while lower IC 50 in the FLISA was obtained (table 2). All these data showed that a one-step FLISA could be developed by using fluobody instead of monoclonal antibody.…”
Section: Comparison Of the Developed Flisa And Traditional Elisasupporting
confidence: 81%
“…In addition, sensitive FLISA can be performed by taking advantage of the strong fluorescence intensity of GFP [48]. Up to date, ic-FLISA can be developed to detect/determine small molecules, which include picloram [49], s-triazine [50], 5-methyl 2'-deoxycytidine [51] and bioactive natural product, plumbagin (PL) and ginsenoside Re (GRe) as previously described in our group [52]- [54]. The icFLISA for PL and GRe shows a lower limit of determination than conventional icELISA.…”
Section: Fluorescence-linked Immunosorbent Assaymentioning
confidence: 99%
“…Currently, the usage of fluobody has been expanded from diagnosis, molecular targeted therapy, immunolabeling of cancer cells, probes for immunoassay, fluorescence-activated cell sorter (FACS) to fluorescent-linked immunosorbent assay (FLISA) for the detection of large molecular weight antigens such as proteins, peptides, and microtubules [47][48][49][50][51]. So far the application of a fluobody in FLISA for the detection of small molecules has been rarely reported except against herbicide, picloram [52] and s-triazine [53], and bioactive natural products, PL and G-Re [54][55][56] previously described by our group.…”
Section: Introductionmentioning
confidence: 99%